Analysis of Escherichia coli O157:H7 Isolates from Beef by RAPD-PCR and Plasmid Profiles - Son, Radu; Rozila, Alias; Gulam, Rusul; Samuel, Lihan; Ooi Wai, Ling (Capricon Publication, 2000)
A total of 70 isolates of Escherichia coli O157:H7 isolated from beef samples were examined with respect to plasmid profiles and random amplified polymorphic DNA (RAPD) patterns. All isolates carried the 90 kb pO157 plasmid alone or in combination with other smaller plasmids. Using Gen1-50-02 (5`-CAATGCGTCT-3`), Gen1-50-09 (5`-AGAGGCGATG-3`) and Gen1-50-10 (5`-CCATTTACGC-3`) as primers, respectively, we obtained DNA polymorphisms which allowed us to discriminate the E. coli O157:H7 isolates into one, six and five RAPD patterns; providing bands ranging in size from 0.25 to 4.0 kb. Our results demonstrate that both plasmid profiling and RAPD-PCR fingerprinting methods are suitable tools for a fast and reliable molecular typing of E. coli O157:H7. The RAPD-PCR method is more sensitive with respect to the individualization of isolates and that RAPD-PCR assay could be a valuable technique for epidemiological studies.